2015
DOI: 10.1038/ncomms7208
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of erosion of nanostructured porous silicon drug carriers in neoplastic tissues

Abstract: Nanostructured porous silicon (PSi) is emerging as a promising platform for drug delivery owing to its biocompatibility, degradability and high surface area available for drug loading. The ability to control PSi structure, size and porosity enables programming its in vivo retention, providing tight control over embedded drug release kinetics. In this work, the relationship between the in vitro and in vivo degradation of PSi under (pre)clinically relevant conditions, using breast cancer mouse model, is defined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(75 citation statements)
references
References 59 publications
4
69
0
Order By: Relevance
“…However, it has been extensively demonstrated that MSV degradation in biological conditions occurs faster in cancer therapy 35,36 than what is needed for tissue engineering applications, inciting the need for the inclusion of MSV in polymer shells or scaffolds. Panels in Figure 8 show the histological evaluation of the tissue surrounding the injection site up to 14 days after injection, compared to the control.…”
Section: Evaluation Of Fitc-bsa Release Kinetics In Vitromentioning
confidence: 99%
“…However, it has been extensively demonstrated that MSV degradation in biological conditions occurs faster in cancer therapy 35,36 than what is needed for tissue engineering applications, inciting the need for the inclusion of MSV in polymer shells or scaffolds. Panels in Figure 8 show the histological evaluation of the tissue surrounding the injection site up to 14 days after injection, compared to the control.…”
Section: Evaluation Of Fitc-bsa Release Kinetics In Vitromentioning
confidence: 99%
“…Using the same experimental model, Nandi et al [35] described by angiography that there is well-organized transimplant angiogenesis and establishment of vascular supply across the bone defects treated with bioactive glass porous struts of 35-40 vol% porosity, prepared from a bioactive glass powder of composition (in wt%) 58.60% SiO 2 , 23.66% CaO, 3.38% P 2 O 5 , 3.78% B 2 O 3 , 1.26% TiO 2 , 9.32% Na 2 O. Nanostructured porous silicon (PSi) also undergoes enhanced degradation in diseased environment compared to healthy state, owing to up-regulation of ROS in the tumor vicinity that oxidize the silicon scaffold and catalyze its degradation [27]. The authors further showed that PSi degradation in vitro and in vivo correlated with healthy and diseased states when ROS-free or ROS-containing medium were used, respectively.…”
Section: Silicon (Si)mentioning
confidence: 99%
“…Meso-porous silica is used widely for delivery of active drug molecules based on physical or chemical adsorption. The small pores greatly enhance the capacity of drug loading [106]. In contrast, non-porous particles deliver molecules through encapsulation or conjugation.…”
Section: Morphological and Physicochemical Characterizationmentioning
confidence: 99%